Important Determinants of Sexual and Reproductive Health of Female Adolescent and Youth in Ghana - Nyantah, Rahmat Opoku (2015)
A Thesis submitted to the Department of Mathematics,Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirement for the Degree of M.Phil Mathematical Statistics.